PERKEMBANGAN PRAGMATIK DALAM PEMEROLEHAN BAHASA ANAK - Fitria Akhyar (LPPM STKIP PGRI Bandar Lampung, 2019)
This study aims to describe theoritically related to the development of pragmatic category languages in children. The subjects studied were dominated by pre-school children (under 7 years). The method used in writing this paper is a literature study. Based on the literature that has been studied, it is found that: (1) in each context of dialogue there is a violation of the maxims with a certain frequency. Some responses from resource persons are straightforward and very informative or have adhered to the maxim of quantity, quality, relevance, and method; (2) the number of violations of maxims carried out by respondents can be seen as something natural and a natural process. (3) children preschool age still use positive politeness strategy to express their wishes.